Customary law, the environment and sustainable development (2019)
"The environment is one of the essential sources for human sustainability. Although the concept of environment is a very wide one, the nexus between customary law and the environment is of great importance. Customary law has been deemed to be of no direct link with the environment and sustainable development. This article considers the linkage and importance of the three concepts, though with wider jurisprudential debates. This article strictly considers importance of customary law to environment and sustainable development in Nigeria as well as United Nations Environmental Programme (UNEP) on the need to engage the indigenous people on achieving basic sustainable development goals. The article uses both indigenous people as well as native people to derive home the importance of the peoples‟ customs and beliefs. To achieve the goals of sustainable development in Nigeria, there is need to incorporate customary laws in Nigeria. The contributions of indigenous people at various ethnic setting in Nigeria are very important, because these people are the custodians of the customary laws which have been made applicable over times on certain aspects of the environment"